Integration of the social and health sectors in Scotland: Assessment of the first 5 years (2014–2018) - Matos, R. C. de.; Nascimento, G. do.; Fernandes, A. C. (Portuguese Journal of Public Health, 2025)
In Western societies, the emergent societal challenges require changes in public policies to manage their consequences and to avoid a demise in public sectors. Public health is a coordinated system that engages the government and multiple stakeholders to protect and improve population health through prevention, policy, and community initiatives [1]. Moreover, it requires a clear framework that defines where leadership should be positioned and at what level it should function [2]. This is essential to develop, implement, and sustain efficient policies and face complex public tasks. In Scotland, during the last decade, there has been an increase of 25% in people over 75 years, the highest number of health and social care service users ever [3]. In 2011, the Scottish government published a manifesto stating it would deliver a single integrated health and social care system across Scotland [4]. To comply with a national health and social care integration (HASCI), in 2014, the government published the Health Care with Social Services: Public Bodies (Joint Working) Act 2014, with guiding norms for regional implementation [5]. HASCI requires health boards and local authorities to partner with the third sector, users, carers, and other key stakeholders. It motivates the creation of a more joined-up care experience for people with health and social care needs. To achieve a more integrated patient experience, health and social care providers often need to integrate at an organizational level [6]. This is critical to sustain the four key areas of HASCI [7], namely, (1) reduce hospital admissions; (2) move toward prevention; (3) promote more personalized health plans; and (4) enable individuals to live more independently [7]. In this sense, the integration of health and social policies is a process that can be achieved through many ways: pooling of funds, strategic planning, functional and organizational consolidations, joint commissioning, service colocation, joint programs, centralized case management and information systems, multidisciplinary teams, shared diagnostic procedures, and patient involvement [8]. Specifically, regarding the healthcare sector, there are four main types of integration: functional, organizational, professional, and clinical, which can occur either horizontally or vertically [9, 10], while most countries have introduced integration schemes to promote professional or clinical collaborations horizontally. This letter examines the integration of the social and health sectors in Scotland, focusing on the first 5 years of implementation following the Health and Social Care Integration policy framework (2014–2018). It specifically analyzes key policy measures and structural changes introduced to facilitate integration, assesses progress based on publicly available outcome data and official reports, identifies challenges and barriers affecting the effectiveness of integration, and discusses future steps to enhance coordination between health and social care services. By examining these early-stage impacts, policymakers, healthcare providers, and stakeholders can make informed decisions about necessary adjustments, ensuring that integration efforts lead to long-term improvements in care delivery. Additionally, understanding initial successes and shortcomings can help refine strategies for future policy development, optimize resource allocation, and enhance the overall effectiveness of integrated health and social care services.